Metabolic heat loss in southern elephant seals (Mirounga leonina) differs with stage of moult and between habitats. (February 2022) - Paterson, William D.; Chaise, Laureline L.; McKnight, Chris; Currie, John I.; Thompson, Dave; Ancel, André; Gilbert, Caroline; McCafferty, Dominic J.
Abstract: The moult in southern elephant seals ( Mirounga leonina ) represents an especially energetically demanding period during which seals must maintain high skin temperature to facilitate complete replacement of body fur and upper dermis. In this study, heat flux from the body surface was measured on 18 moulting southern elephant seals to estimate metabolic heat loss in three different habitats (beach, wallow and vegetation). Temperature data loggers were also deployed on 10 southern elephant seals to monitor skin surface temperature. On average, heat loss of animals on the beach was greater than in wallows or vegetation, and greater in wallows than in vegetation. Heat loss across all habitats during the moult equated to 1.8 x resting metabolic rate (RMR). The greatest heat loss of animals was recorded in the beach habitat during the late moult, that represented 2.3 x RMR. Mass loss was 3.6 ± 0.3 kg day -1, resulting in changes in body condition as the moult progressed. As body condition declined, skin surface temperature also decreased, suggesting that as animals approached the end of the moult blood flow to the skin surface was no longer required for hair growth. Highlights: Metabolic heat loss in moulting southern elephant seals differed between terrestrial habitats. Greatest heat loss was in beach habitat during the late moult. Heat loss was lower in wallow and lower still in vegetation habitats. Body condition and skin temperature both decreased at the end of the moult.